2020
DOI: 10.2196/16835
|View full text |Cite
|
Sign up to set email alerts
|

Portals of Change: How Patient Portals Will Ultimately Work for Safety Net Populations

Abstract: Despite the implementation of internet patient portals into the safety net after the introduction of the Affordable Care Act in the United States, little attention has been paid to the process of engaging vulnerable patients into these portals. The portal is a health technology tool that was developed with a mainstream, English-speaking audience in mind. Thus, there are valid concerns that such technologies will actually exacerbate health care disparities, conferring further advantages to the already advantage… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
25
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
2
1

Relationship

1
9

Authors

Journals

citations
Cited by 27 publications
(26 citation statements)
references
References 37 publications
1
25
0
Order By: Relevance
“…22,47 For barriers in digital literacy, robust evidence exists for interventions to support individual-level patient preparation for portal access, which is likely to extend to telemedicine as well. [48][49][50][51][52] For limited English proficiency patients, dissemination of best practices for interpreter services must be standardized. 24 Finally, the design of telemedicine platforms and instructional tools must engage patients and stakeholders from vulnerable populations, applying user-centered design or other participatory methods.…”
Section: Discussionmentioning
confidence: 99%
“…22,47 For barriers in digital literacy, robust evidence exists for interventions to support individual-level patient preparation for portal access, which is likely to extend to telemedicine as well. [48][49][50][51][52] For limited English proficiency patients, dissemination of best practices for interpreter services must be standardized. 24 Finally, the design of telemedicine platforms and instructional tools must engage patients and stakeholders from vulnerable populations, applying user-centered design or other participatory methods.…”
Section: Discussionmentioning
confidence: 99%
“…Third, it is clear from the patient participation rate that we must learn more about how to encourage patients to take advantage of new opportunities to provide information to their clinicians outside of time-pressured encounters. For many, this involves registering more patients on patient portals, particularly those from vulnerable populations, and ensuring that they have adequate access, education, and support to use the portal [ 20 , 21 ]. Today, many patients fill out forms on paper or tablet computers in the waiting room [ 22 ].…”
Section: Discussionmentioning
confidence: 99%
“…Previous research shows that Medicare claim measures of dementia based on International Classification of Disease (ICD) coding lack sensitivity, especially for men, younger adults, and racial/ethnic minorities. [1][2][3][4][5][6] One study found that the validity of the dementia measure based on Medicare claims data increased between 2006 and 2012 and…”
Section: Introductionmentioning
confidence: 99%